Audism unveiled - Bahan, Benjamin J.; Bauman, H-Dirksen L., 1964-; Montenegro, Facundo, 1966-2005; Darnall, Linsay, Jr; Steinberg, Emily Jane.; Dawn Pictures; Black Mountain (Firm); DawnSignPress ([San Diego, CA] : DawnSign Press, 2008)
"This powerful documentary uses real life experiences from Deaf people of varied social, racial, and educational backgrounds showing how audism does lasting and harmful damage."--Container.
Introduction -- Audism: family -- Audism: cure -- Audism: education -- Audism: resistance.
DVD-R; NTSC; region free; 1.33:1 full frame; single layer format.
In sign language with optional English, Spanish, or Canadian French subtitles.
No audio.
Narrated by Linsay Darnall, Jr.
Edited by Facundo Montenegro, Emily Jane Steinberg.
Originally produced as a motion picture in 2006.
Keywords: Deaf people -- Social conditions; Deaf people -- Civil rights; Discrimination against people with disabilities; Documentary films; Nonfiction films; Feature films; Video recordings for the hearing impaired; Feature films -- United States